Clinical implications of immune‐mediated diseases in children with Down syndrome. Issue 2 (25th October 2019) - Verstegen, Ruud H. J.; Chang, Krystal J. J.; Kusters, Maaike A. A.
Abstract: Children with Down syndrome have changes in their innate and adaptive immunity, which contribute to increased rates of infections, autoimmune diseases, and haematological malignancies. While improved care for congenital heart disease has decreased mortality and morbidity, complications related to immune‐mediated diseases continue to limit the life expectancy in Down syndrome. Infectious diseases are common and have a significant effect on development, behaviour and quality of life. Infection frequency and severity are influenced by various anatomical and physiological alterations in addition to immunological changes in Down syndrome. Thus, prevention of respiratory tract infections requires a multifactorial approach. This could include additional active and/or passive immunizations, prophylactic antibiotics, immunoglobulin replacement and ear, nose and throat surgical interventions. Autoimmune conditions like coeliac disease, type I diabetes mellitus and thyroid disease are classically mentioned in the context of Down syndrome. However, autoinflammatory conditions are more prevalent as well. Screening for autoimmune diseases is required and immunosuppression has to be used with caution. Future studies should address optimal screening programmes for immune‐mediated diseases in individuals with Down syndrome, as well as the effect of immune modulation, to further decrease morbidity and mortality, and improve the quality of life of individuals with Down syndrome.